Kinetic investigation and numerical modelling of CaCO3/Al2O3 reactor for high-temperature thermal energy storage application - Mathew, Arun; Nadim, Nima; Chandratilleke, Tilak T.; Paskevicius, Mark; Humphries, Terry D.; Buckley, Craig E. (Elsevier, 2022)
This study conducts kinetic analyses of the carbonation reaction of CaCO3 (doped with Al2O3) as well as parametric analyses of the performance of a thermochemical reactor, which can act as a thermal battery. Kinetic measurements of CO2 release and absorption were carried out using thermogravimetric analysis (TGA) at 815, 830 and 845 °C on a CaCO3/Al2O3 sample that had been previously cycled over 500 times. The rapid reaction kinetics revealed that the Avrami nucleation growth model with exponent 3 fits well to explain the carbonation reaction. The numerical study considered a cylindrical reactor with a height and diameter of 100 mm. According to numerical analysis, at an applied CO2 pressure of 1 bar, increasing the thermal conductivity of the reactor bed from 1.33 to 5 W/m.K increases the rate of carbonation reaction by 74%. When the applied CO2 pressure is increased from 1 to 2 bar, the performance of the reactor bed with thermal conductivity of 1.33 W/m.K improves by 42%; however, when the applied CO2 pressure is increased from 2 to 3 bar, the performance improves by only 18%. Additionally, when the boundary temperature of the reactor was lowered by 30 °C, performance was enhanced by 43% at an applied CO2 pressure of 1 bar. This study also examined the effect of using a graphite fin as a heat extraction system. The graphite fin allowed for more rapid heat extraction and increased the carbonation reaction by 44% in the reactor bed with poor thermal conductivity (1.33 W/m.K) but had no effect in the reactor with modest thermal conductivity of (5 W/m.K) due to its ability to already transfer heat effectively to the reactor shell.